Development of economic analysis - Rima, Ingrid Hahne (Homewood, Ill. : R. D. Irwin, 1978)
This is the sixth edition of a textbook that has been instrumental in introducing a generation of students to the history of economic thought. It charts the development of economics from its establishment as an analytical discipline in the eighteenth century through to the late twentieth century. The book discusses the work of, amongst others: Ricardo, Malthus, Marx, Walras, Marshall and Keynes as well as the institutionalists, the Chicago School and the emergence of econometrics. This edition has been fully revised and updated and includes:* chronologies of the key dates in the development of.
Includes indexes.
Bibliography: p. 20-22.
aia 16/10/17
Loans
Keywords: Economics